Factors associated with mortality in Scottish patients receiving methadone in primary care: retrospective cohort study. (17th June 2009) - McCowan, C; Kidd, B; Fahey, T
Abstract : Objective To assess predictors of mortality in a population of people prescribed methadone. Design Retrospective cohort study. Setting Geographically defined population in Tayside, Scotland. Participants 2378 people prescribed and dispensed liquid methadone between January 1993 and February 2004. Main outcome measures All cause mortality (primary outcome) and drug dependent cause specific mortality (secondary outcome) by means of Cox proportional hazards models during 12 years of follow-up. Results Overall, 181 (8%) people died. Overuse of methadone (adjusted hazard ratio 1.67, 95% confidence interval 1.05 to 2.67), history of psychiatric admission (2.47, 1.67 to 3.66), and increasing comorbidity measured as Charlson index ≥3 (1.20, 1.15 to 1.26) were all associated with an increase in all cause mortality. Longer duration of use (adjusted hazard ratio 0.95, 0.94 to 0.96), history of having urine tested (0.33, 0.22 to 0.49), and increasing time since last filled prescription were protective in relation to all cause mortality. Drug dependence was identified as the principal cause of death in 60 (33%) people. History of psychiatric admission was significantly associated with drug dependent death (adjusted hazard ratio 2.41, 1.25 to 4.64), as was history of prescription of benzodiazepines (4.35, 1.32 to 14.30). Conclusions Important elements of care in provision of methadone maintenance treatment are likely to influence, or be a marker for, a person's risk of death.